2014
DOI: 10.1136/bcr-2014-204347
|View full text |Cite
|
Sign up to set email alerts
|

Conservative management of persistent facial cutaneous sinus tract with a dental origin

Abstract: Facial and cervical area sinus tracts can be odontogenic or non-odontogenic, and so clinicians should be aware that lesions with a dental origin can be confused with dermatological lesions. We describe three cases of cutaneous lesions of dental origin that were initially misdiagnosed as being dermatological in origin. Multiple unsuccessful treatments were attempted but the lesions failed to heal. However, conservative endodontic intervention resulted in complete resolution of the causative periapical lesions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…According to Janev and Redzep, [3] after root canal treatment, apical resection and extraoral excision were performed and total recovery was observed. Kumar et al [4] reported that sinus tracts of dental origin completely resolved only with conservative endodontic treatment similar to that observed by Tidwell et al [5], Pasternak-Júnior et al [9], and Tian et al [10]. According to Giménez-García et al [11] in the first case, extraction of the remains of several roots and extraoral excision was performed; in the second case, it was too late for endodontic treatment; therefore, the tooth with cyst was extracted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Janev and Redzep, [3] after root canal treatment, apical resection and extraoral excision were performed and total recovery was observed. Kumar et al [4] reported that sinus tracts of dental origin completely resolved only with conservative endodontic treatment similar to that observed by Tidwell et al [5], Pasternak-Júnior et al [9], and Tian et al [10]. According to Giménez-García et al [11] in the first case, extraction of the remains of several roots and extraoral excision was performed; in the second case, it was too late for endodontic treatment; therefore, the tooth with cyst was extracted.…”
Section: Discussionmentioning
confidence: 99%
“…Frequently, the possibility of an odontogenic origin is overlooked so that patients prefer to refer to physicians for treatment of the cutaneous lesion, because most of the patients do not experience any symptoms associated with teeth [3]. Many patients can also show similar conditions in specific clinical anomalies such as epidermal cyst, furuncle, carbuncle, foreign body reaction, osteomyelitis, bisphosphonate-associated osteonecrosis, pyogenic granuloma, salivary gland fistula, thyroglossal tract fistula, branchial cleft fistula, actinomycosis, basal cell, and squamous cell carcinoma [14]. In this instance, physicians may not appreciate the chronic dental infection as the source of a draining sinus tract, and therefore, treatment may involve therapies directed at nonodontogenic diagnosis such as multiple antibiotic regimens, multiple surgical excisions, multiple biopsies, and radiotherapy, all of which failed [16].…”
Section: Introductionmentioning
confidence: 99%
“…[4] This concept is almost always true; however, in our practice, we have confronted with two cases that need to local skin flaps for solving the problem of depressed scar on the face several months after resolution of odontogenic source of infection.…”
mentioning
confidence: 99%
“…More often than not, the literature delivers the same message; that the lesions are diagnosed incorrectly and thus treated late and ineffectively. The cutaneous tracts tend to occur more frequently as a result of infected mandibular teeth (80%) more than infected maxillary teeth (20%) (1)(2)(3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…They undergo multiple surgical excisions or biopsies which cause unnecessary scarring, further courses of antibiotic therapy, and even occasional radiotherapy with eventual recurrence of the cutaneous sinus tract and all because the primary dental cause is frequently misdiagnosed. However, if the correct diagnosis of the sinus tract is identified, the problem can be managed with a simple and effective treatment that comprises removal of the infected pulp canal tissue, which subsequently results in minimal cutaneous scarring (2,3,5,6,(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%